Phosphoric acid loaded azo (-N=N-) based covalent organic framework for proton conduction - Chandra, Suman; Kundu, Tanay; Kandambeth, Sharath; BabaRao, Ravichandar; Marathe, Yogesh N.; Kunjir, Shrikant M.; Banerjee, Rahul (Journal of the American Chemical Society, 2014)
Two new chemically stable functional crystalline covalent organic frameworkds (COFs) (Tp-Azo and Tp-Stb) were synthesized using the Schiff base reaction between triformylphloroglucinol (Tp) and 4,4'-azodianiline (Azo) or 4,4'-diaminostilbene (Stb), respectively. Both COFs show the expected keto-enamine form, and high stability toward boiling water, strong acidic, and basic media. H3PO4 doping in Tp-Azo leads to immobilization of the acid within the porous framework, which facilitates proton conduction in both the hydrous (sigma = 9.9 X 10(-4) S cm(-1)) and anhydrous state (sigma = 6.7 X 10(-5) S cm-1). This report constitutes the first emergence of COFs as proton conducting materials.

Role of the molecular structure of carboxylate-alumoxanes in the enhanced nucleation of polypropylene - Mani, Mohan Raj; Chellaswamy, Ramesh; Marathe, Yogesh N.; Pillai, Vijayamohanan K. (Chemical Communications, 2015)
We have reported the use of carboxylate-alumoxanes as efficient nucleating agents for isotactic polypropylene (iPP) with a possible structural correlation to the nucleation efficiency. The unique, butterfly-like structure of carboxylate-alumoxanes correlates well with the nucleation characteristics of iPP and, for the first time, the impact of a thermally induced, crystalline transition of carboxylate-alumoxanes, which alters neither the structural conformation nor the nucleation efficiency of the transformed material, is demonstrated.

Enhanced nucleation of polypropylene by metal-organic frameworks (MOFs) based on aluminium dicarboxylates: influence of structural features - Mani, Mohan Raj; Chellaswamy, Ramesh; Marathe, Yogesh N.; Pillai, Vijayamohanan K. (RSC Advances, 2016)
Metal-organic frameworks (MOFs) based on aluminium dicarboxylates provide a new platform for the enhanced nucleation of isotactic polypropylene (iPP). For instance, aluminium dicarboxylates exhibit a unique butterfly-like structure similar to that of carboxylate-alumoxanes and correlates well with the nucleation characteristics of iPP. A subtle change in the structure of the ligand backbone (fumarate/succinate) does not alter the framework structure despite changing the hydrophilic/hydrophobic character and its subsequent nucleation characteristics. This suggests that the nucleating agent should facilitate favourable interaction with hydrophobic iPP for efficient nucleation. Further, a systematic variation of the alkyl chain length in the Al-dicarboxylate does not change the nucleation efficiency considerably, even though it increases the distance between the octahedral alumina chains in the metal-organic framework, suggesting that the butterfly-like structure present in the framework is a key aspect for nucleation. Finally, the significance of the orientational conformation of the dicarboxylate around the metal centre for the nucleation is confirmed by the poor nucleation efficiency of chromium and zirconium suberate MOFs where the orientation of suberate would be different from that of aluminium suberate due to the difference in the ligation of the carboxylate group. The present work thus provides valuable pathways for developing new nucleating agents based on MOFs with appropriate selection and orientation of the organic linkers around the metal centre.

New understanding on regulating the crystallization and morphology of the beta-polymorph of isotactic polypropylene based on carboxylate-alumoxane nucleating agents - Mani, Mohan Raj; Chellaswamy, Ramesh; Marathe, Yogesh N.; Pillai, Vijayamohanan K. (Macromolecules, 2016)
Carboxylate alumoxane derived from p-n-alkylbenzoic acids, where n-alkyl group changes from 2 to 8 carbon atoms, exhibits dual nucleating ability and nucleates isotactic polypropylene (iPP) into predominantly in the beta-phase under specific conditions. The selectivity of the beta-phase nucleation depends on the concentration of the nucleating agent, end melting temperature and cooling rate. The beta-phase obtained from p-n-alkylbenzoate-alumoxanes is compared with the beta-phase obtained from calcium pimelate (CaP), an efficient beta-phase selective, nucleating agent, using the results from DSC, WAXS, and SAXS analysis. The lamellar morphology of iPP nucleated with different nucleating agents crystallized at different crystallization temperatures (T-C) under controlled nonisothermal conditions are evaluated using SAXS analysis. The long period increases with increasing crystallization temperature and the long period of the beta-phase is always larger than that of the alpha-phase for a given crystallization temperature. Furthermore, the variation of long period with crystallization temperature clearly brings out two crystallization temperature ranges; the low temperature range and the high temperature range. However, the beta-phase shows a lower changeover temperature compared to that of the alpha-phase. The one-dimensional correlation analysis of the beta-phase shows that the thickness of the crystal lamellae (lc) increases with T-C and exhibits the low and high crystallization temperature ranges, while the thickness, of the amorphous layer (la) more or less remains constant. In-situ high temperature WAXS studies capture the beta-phase to the a-phase transition and the transformed material con-elates well with the lamellar thickness of the beta-phase. The morphological difference between the alpha- and the beta-phases are discussed and attributed to the differences in the impact properties and the melting temperature. This study clearly demonstrates that the lamellar morphology mainly depends on the T-C and not on the nature of the nucleating agents.

Electrospun poly(3-hydroxybutyrate-co-3-hydroxyvalerate)/polyethylene oxide (PEO) microfibers reinforced with ZnO nanocrystals for antibacterial and antibiofilm wound dressing applications - Mahamuni-Badiger, Pranjali P.; Patil, Pooja M.; Patel, Pratikshkumar R.; Dhanavade, Maruti J.; Badiger, V. Manohar; Marathe, Yogesh N.; Bohara, Raghvendra A. (New Journal of Chemistry, 2020)
Biocompatible and biodegradable polymers are extensively used in designing wound dressing materials. The present investigation deals with the preparation of a unique blend of zinc oxide (ZnO) nanoparticles incorporated in poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV)/polyethylene oxide (PEO) microfibersviaan electrospinning technique for antibacterial, antibiofilm and wound dressing applications. This composite was prepared by incorporating previously synthesized ZnO NPs with better antibacterial and antibiofilm activity in PHBV-PEO (4 : 1) polymers in chloroform solution. Scanning electron microscopy (SEM) and Fourier transform infrared (FT-IR) spectroscopy confirmed that ZnO NPs were incorporated in the PHBV-PEO microfibers. The synthesized microfibers exhibited enhanced mechanical properties after the incorporation of ZnO NPs. The results of antibacterial and antibiofilm activity of the prepared microfibers revealed that the incorporated ZnO NPs in different concentrations (1%, 3%, and 5%) showed different degrees of antibacterial activity against pathogenic Gram-positiveStaphylococcus aureus(NCIM 2654) and Gram-negativePseudomonas aeruginosa(NCIM 5032), which are the main bacteria found in wound infections. The PHBV-PEO-ZnO microfibers exhibited excellent hemocompatibility with improved swelling behavior after the incorporation of ZnO NPs.In vitrocytotoxicity assays revealed the non-toxic nature of the prepared PHBV-PEO-ZnO microfibers. The current work confirms that utilizing a unique blend of the biodegradable, biocompatible, thermoplastic and hydrophobic natural polymer PHBV with hydrophobic, biodegradable, non-toxic and synthetic polymer PEO with ZnO NPs holds great potential for use as an antibacterial and antibiofilm material for wound dressing applications.

Synthesis and characterization of nylon 6 polymer nanocomposite using organically modified Indian bentonite - Kumaresan, S.; Rokade, Dhammaraj S.; Marathe, Yogesh N.; Ingole, Pravin G.; Pawar, Radheshyam R.; Pol, Harshawardhan V.; Bajaj, Hari C. (SN Applied Sciences, 2020)
In this present research work two different organic compounds are applied for the modification of Indian origin bentonite. One is with n-hexadecyltrimethylammonium bromide (CTAB), intercalated with an interlayer of bentonite via cation exchange mechanism. Whereas, another with 3-Aminopropyl trimethoxysilane (APTES) interlayer functionalization with bentonite –OH group. APTES and CTAB–intercalated bentonites samples were further cross modified with CTAB and APTES to obtain novel co-surfactant locked organo bentonite modeling (CLOM) like matrices. Original and modified bentonite samples were comparatively evaluated by advanced characterization techniques such as, powder X-ray diffraction, Fourier-transform infrared spectroscopy, thermal gravimetric analysis (TGA). Moreover, the applicability of the developed CLOM like materials were investigated in nylon 6 nanocomposite preparation by melt compounding method using a micro twin co-rotated extruder. Additionally, CLOM-nylon-6 polymer nanocomposites were characterized by wide angle X-ray diffraction, TGA, differential scanning calorimetry, atomic force microscopy and tensile strength measurement. The observed thermograph results confirmed no significant difference in the thermal properties of the developed composites. Whereas, the significant variation observed in the tensile strength results particularly for developed composite 5% of N6-OAMSB and N6 AMOSB 5 showed 111.5 and 76.6% respective enhancement in tensile strength results when compared with a bare nylon-6 polymer.